Biotechnology and the CGIAR - Pinstrup-Andersen, Per; Cohen, Marc J. (Friends of the Earth Europe, 2003)
In this paper, the authors offer general background information on the CGIAR and the role of agricultural research in poverty eradication. They then examine the current state of biotechnology research within the system, current and potential research partnerships (with an emphasis on civil society and the private sector), and constraints that lie ahead.